Identification of emotion schemes in women with premenstrual dysphoric disorder (PMDD) using an emotion-focused therapy (EFT) approach: A qualitative study - Saeideh Izadi Dehnavi; Seyede Salehe Mortazavi; Mohammad Arash Ramezani; Banafshe Gharraee; Ahmad Ashouri (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: In women with premenstrual dysphoric disorder (PMDD), emotional problems constitute most of their symptoms. This study aimed to identify the emotion schemes of women with PMDD and to determine the core emotional pains at the center of the emotion scheme of PMDD to facilitate the treatment of this disorder using an emotion-focused therapy (EFT) approach. MATERIALS AND METHODS: This study was performed using the directed content analysis method by Hsieh and Shannon. The participants were selected by purposive sampling. The Premenstrual Symptoms Screening Tool (PSST) was used for the primary diagnosis of women, and the Structured Clinical Interview for DSM-5 (SCID-5) was conducted for the final diagnosis. A total of 10 participants were examined via in-depth interviews in this study. The emotion scheme matrix was used as a framework to identify the emotion scheme of PMDD. RESULTS: Based on the emotion scheme matrix, the participants' experiences were classified into two main themes, four categories, and eight subcategories, with 37 extracted codes. CONCLUSION: Based on the present results, the primary and secondary emotions and behaviors in women with PMDD indicated perceptual-situational, bodily-expressive, motivational-behavioral, and symbolic-conceptual elements in line with the core emotional pains of desperation, despair, and feelings of worthlessness based on the primary maladaptive scheme of shame, which is responsible for different psychological symptoms.